PENGARUH SDGS, INTELLECTUAL CAPITAL DAN UKURAN PERUSAHAAN TERHADAP KINERJA KEUANGAN PERUSAHAAN (STUDI EMPIRIS PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BEI PERIODE 2018-2021) - Janah, Fajarina Miftakhul; Maryono; Rr. Tjahjaning Poerwati (Jurnal Riset Akuntansi Politala, 2024)
This study aims to find empirical evidence that can reduce  the research gap and  analyze the effect of SDGs, Intellectual Capital, and company size on the company's financial performance. The samples in this study are manufacturing companies listed on the Indonesia Stock Exchange (IDX) for the 2018-2021 period with a total of 136 samples that can be processed. In this study, data analysis used multiple linear regression analysis with the help of IBM Statistics SPSS v25. Research that has been conducted on SDGs on the company's financial performance can be concluded that this variable has a significantly positive  effect on the company's financial performance. The Intellectual Capital variable  shows the results that Intellectual Capital measured by VAIC is stated to have a significant effect on the company's financial performance. Meanwhile, the variable size of  the company has no effect on the company's financial performance.